PUIG DE LA BELLACASA, María Puig. “Matters of Care: Speculative Ethics in More Than Human Worlds”. Minneapolis: University of Minnesota Press, 2017. - Ferreira, Amanda Finotti Lagos (Revista de Antropologia da UFSCar, 2024)
<span class="TextRun SCXW101128518 BCX2" lang="PT-BR" style="font-size: 12pt; line-height: 28.5px; font-family: Times New Roman, 'Times New Roman_EmbeddedFont', 'Times New Roman_MSFontService', serif; font-weight: bold;" xml:lang="PT-BR" data-contrast="auto">PUIG DE LA BELLACASA, María Puig. “Matters of Care: Speculative Ethics in More Than Human Worlds”. Minneapolis: University of Minnesota Press, 2017.